It's a Small World After All: Western Usability Guidelines Predict Behavior of Chinese Users of On-Line Bookstores - Yau, Josephine K.Y.; Hayward, William G. (ANIMA Indonesian Psychological Journal, 2005)
The present study examined whether Western usability guidelines apply to Chinese websites. Nielsen et al (2000) proposed a set of 207 usability guidelines derived from observations in the field. We took a subset of 48 rules, and looked at the compliance rate (number of guidelines a website complied with, divided by the total number of guidelines), task completion time, task accuracy, and users' perceived usability and likeability for four Chinese online bookstores. Results showed a clear relationship between adherence to the rules and usability of the site: as the website's compliance rate increased, so did the usability and the impression the web site received from its users. These results suggest that the rules governing behavior of Chinese users are similar to those of Western users. More generally, this study calls into question the widely-held intuition that usability for Asian websites should be different than usability for Western sites. Studi ini meneliti apakah pedoman penggunaan dari Barat berlaku juga untuk situs-situs jaringan (websites) China. Nielsen et al. (2000) mengumpulkan 207 pedoman penggunaan yang diperoleh dari observasi dilapangan. Kami mengambil subset dari 48 aturan, dan melihat padajumlah kepatuhan (jumlah pedoman yang cocok dengan suatu situs jaringan, dibagi jumlah total pedoman), waktu penyelesaian tugas, keakuratan tugas, dan kegunaan dan kesukaan yang dirasakan pemakai untuk empat toko buku China on-line. Hasil- hasil menunjukkan hubungan yang jelas antarakepatuhan pada aturan dan kegunaansitus: bilalaju kepatuhan padasitus jaringan meningkat, demikian pulakegunaan dan kesanyang diterimasitus jaringan dari penggunanya Hasil-hasil ini menyiratkan bahwa aturan yang mengatur perilaku pengguna China mirip dengan aturan untuk penggunaorang-orang Barat. Sebenarnya, studi ini mempertanyakan intuisi yang banyak diyakini bahwapenggunaan situs-situs jaringan untukorang-orang Asiaharus berbeda dari yang untuk orang-orang Barat.